EVALUATION OF AUTENTIC AUTHENTICAL ASSESSMENT ON LEARNING ON THE LEARNING RESULT OF PARTICIPANTS CLASSIFIED VIII SMP NEGERI 3 SALATIGA - Andriyani Dea Wulandari; Risya Pramana Situmorang; Lusiawati Dewi (Pendidikan Kimia Unimus, 2018)
This study aims to determine the authenticity of the assessment and to know its relationship with learning outcomes. This research was conducted in SMP Negeri 3 Salatiga. The research method used is survey method with stake's countenance model. The subjects of the study were IPA teachers who used authentic assessment in evaluating learners' learning outcomes. Data retrieval using an authentic assessment appraisal observation sheet. Data analysis using score calculation and correlation analysis using spearman test. The results of the calculation of the scores obtained an authentic assessment on the knowledge aspects of the planning phase is very less, the implementation stage is very good, and the results of learning good. In the attitude aspect of the planning stage is good, the implementation stage is very good, and the learning result is very less. In the skill aspect of the planning stage is good, the implementation stage is very good, the learners learn good result. While the results of correlation analysis, which shows a significant correlation only the planning and learning outcomes of learners